1989
DOI: 10.3402/tellusa.v41i2.11826
|View full text |Cite
|
Sign up to set email alerts
|

The effect of parameterized ice microphysics on the simulation of vortex circulation with a mesoscale hydrostatic model

Abstract: It has been proposed that ice microphysics, particularly the melting effect, can play an important rde in the generation of mesoscale structure and evolution of convective weather systems and associated stratiform rainfall. In this paper, parameterized cloud ice and snow crystals are incorporated into an explicit (grid-resolved) convective scheme as prognostic variables and tested using an observed mesovortex on a grid resolution of 25 km. With the inclusion of ice microphysics parameterization. the resolvable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…A sensitivity experiment, in which ice phase was turned off from the control simulation, indicates that the simulated hurricane is 8-10 hPa stronger than the control one at the end of the 72-h integration (not shown), suggesting the importance of the sublimative and melting cooling in suppressing the storm. This is similar to that discussed by Zhang (1989) in association with the development of a midlevel mesovortex. The evaporative cooling rates, peaked in the MBL near the outer edge of the eyewall, range between 1-3ЊC h Ϫ1 .…”
Section: Potential Temperature Budgetssupporting
confidence: 90%
“…A sensitivity experiment, in which ice phase was turned off from the control simulation, indicates that the simulated hurricane is 8-10 hPa stronger than the control one at the end of the 72-h integration (not shown), suggesting the importance of the sublimative and melting cooling in suppressing the storm. This is similar to that discussed by Zhang (1989) in association with the development of a midlevel mesovortex. The evaporative cooling rates, peaked in the MBL near the outer edge of the eyewall, range between 1-3ЊC h Ϫ1 .…”
Section: Potential Temperature Budgetssupporting
confidence: 90%
“…The model water cycles used for this study include (1) a simple ice microphysics scheme for grid‐scale precipitation with the prognostic equations for cloud water, cloud ice, rain water and snow [ Zhang , 1989; Dudhia , 1989]; (2) the newest version of the Kain‐Fritsch (KF2) convective parameterization scheme for subgrid scale convection including the effects of shallow convection [ Kain , 2004]; (3) the Eta model's Mellor‐Yamada planetary boundary layer (PBL) scheme [ Janjić , 1994]; (4) a long‐ and short‐wave radiation scheme which interacts with the atmosphere, cloud, and land surface [ Dudhia , 1989]; and (5) the NCEP‐Oregon State University‐Air Force‐Hydrologic Research Lab (NOAH) land surface model [ Chen and Dudhia , 2001a, 2001b].…”
Section: Model Descriptionmentioning
confidence: 99%
“…Using a two-dimensional (2D) model, Brown (1979) demonstrated that cloud evaporative cooling could induce mesoscale downdrafts beneath the anvil clouds. With a mesoscale hydrostatic model, Zhang (1989) studied the sensitivity of the simulated MCSs associated with the July 1977 Johnstown flood to a twoclass (cloud ice and snow) ice microphysics scheme. He found that freezing and depositional growth assist the development of a midlevel warm-core vortex, while the subcloud-layer melting weakens the concentration of cyclonic vorticity and its associated low pressure system in the lower troposphere.…”
Section: Introductionmentioning
confidence: 99%